Touchstone class audio : (Cambridge University Press, 2006)
Easy and enjoyable to teach, Touchstone is packed with new and exciting ideas, offering a fresh approach to the teaching and learning of English. Student's Book 2 is second level of the innovative Touchstone series designed for high-beginning students and it expands on the fundamental concepts established in Student's Book 1. Drawing on research into the Cambridge International Corpus, Student's Book 2 presents the vocabulary, grammar, and functions students encounter most often in real life. It also develops the conversation strategies that students need for effective conversations, such as how to say no in a friendly way or how to respond to suggestions you are not sure about. The book features an attractive, contemporary design, and beautiful color photos and illustrations. It makes learning fun by maximizing the time students spend on interactive, personalized activities on high-interest topics. Students using Touchstone will soon feel confident in their abilities to express themselves clearly and effectively. A free self-study Audio CD/CD-ROM at the back of the book gives students further practice in listening, speaking, and vocabulary.